A little more on visual images in contemporary education and visual culture - Victorio Filho, Aldo (2018)
This article has been conceived to be one more contribution to the updating and strengthening of the reflection on visual image in contemporaneity in the scope of the Visual Arts teaching in basic education. That is to say its main meanings and its most outstanding uses and risks to school education. The effort contained here is motivated by the need to advance the elucidation of the relations between art and the imaginary universe, an indispensable problematization to the aforementioned reflection on the visual image, through the perspective of photography and the teaching of Visual Arts in the contemporary flow of Visual Culture.